Against Epistemic Domination: A Review of the Decolonization of Qur'anic Studies and the Inclusivity of Knowledge - Achmad Syariful Afif; Abdullah Khoirur Rofiq; Adam Annural Haj (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Decolonization of Al-Quran studies is a approach that aims to examine, challenge and overcome interpretations and methodologies that are influenced by the hegemony of knowledge, especially by